Continuity With a Difference: Rising to Prominence. (1st March 2021) - Finch, Paul
Abstract: Architectural journalist, publisher and founder of the World Architecture Festival Paul Finch charts the ebbs and flows of the post‐Second World War London architectural scene and its genealogy. He shows where AHMM fits into this family tree, but also how their embracing of 'generalism' and 'good architecture' applied to the everyday has set them apart from some of their peers.